PEMBERIAN PUPUK BOKASHI DENGAN DOSIS BERBEDA PADA MEDIA AIR LIMBAH RUMAH TANGGA TERHADAP PERKEMBANGAN POPULASI Moina sp - Candra Muhasdika; Rosyadi Rosyadi; T Iskandar Johan (DINAMIKA PERTANIAN, 2015)
The objective of tis esearch was to know the bokashi fertilizer use with different dosages od household waste water media on population development of Moina sp. The research was conducted at the fish breeding centre of Faculty of Agricuoture Riau Islamic University Pekanbaru from April to May 2014. The materials used were Moina sp, cow dung, and rice bran and containers used topless, household waste water. The completely randomized design was used with four treatments, namely P0 (without bokashi), P1 (dosage of 0.5 g/l), P2 (dosage of 1 g/l), and P3 (dosage of 1.5 g/l) and three replecation. The result showed that the highest population was found on the treatment with dosage of 1 g/l and occurred on 8th day with population numbers of 13,440 ind/l. The lowest population was found on the treatment of bokashi fertilizer use with peak population occurred on 6th day with population number of 4,260 ind/l. Based on varian analysis, the using of bokashi fertilizer with different dosage of household waste water madya for population development of Moina sp was found a sifnificant difference (99%). The water quality of madia culture during research such as temperature (26 – 280 C), pH (6.0 – 7.0),DO (5.25 – 6.00 ppm), and NH3 (0.19 – 1.85 ppm with water quality is still feasible for supporting survive and propogation of Moina sp.